Perception of Merchants and Consumers Towards Payments Using Qris for UMKM in Mataram - Mar’atun Sa’diah (STKIP Taman Siswa Bima, 2024)
The number of QRIS users in West Nusa Tenggara (NTB) has reached 475 thousand, with Mataram City as the region with the largest number of merchants, namely 87,593 merchants. With QRIS, merchants no longer need to provide many QR Codes to serve buyers because with 1 QR Code with the QRIS logo you can read all non-cash payment applications, to simplify QR Code-based non-cash payments. In the era of the Industrial Revolution 4.0, MSMEs must switch to digital so as not to be left behind in terms of payment systems. This research aims to find out, first, the history of Bank Indonesia launching QRIS as a unifying tool for the QR Code Non-Cash Payment System, second, the implementation of QRIS as a driver to realize the vision of the Indonesian Payment System 2025, and third, traders' perceptions of the use of QRIS as a transaction tool for MSMEs in Mataram. The research approach in this study is descriptive qualitative with data collection methods, namely observation, interviews, documentation and literature study. The research results concluded that first, Bank Indonesia launched QRIS on August 17 2019 to simplify QR Code-based non-cash payments. Second, QRIS is one of the initiatives to realize the Indonesian Payment System 2025 and Third, QRIS helps merchants (MSMEs) to make more practical, fast and safe payments and encourages merchants to save part of their income, but according to the results of the author's interview, there are still few people who using non-cash payments and there are still many who don't know what QRIS is.